Evaluación de calidad organoléptica de micro silos con pasto elefante (Pennisetum purpureum) y botón de oro (Tithonia diversifolia) en la provincia de Misiones = Organoleptic quality evaluation of micro silos with elephant grass (Pennisetum purpureum) and buttercup (Tithonia diversifolia) in the provincie of Misiones - Gonzalez, Paola Analia; Barth, Sara Regina; Sosa, Hernán; Colcombet, Luis; Picot, José; López, Agustina; Stoll, Adrián (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2025)
Livestock activity in Misiones covers some 380 thousand heads; one of the production restrictions is the availability of forage quantity and quality, especially in winter. The work proposes to evaluate forage preserved as silos, with mixtures of Pennisetum purpureum and Tithonia diversifolia and through a subjective evaluation observing organoleptic characteristics (color, smell, texture) and pH data, determine its quality. Once the micro silos were opened, it was possible to observe that the organoleptic characteristics were between good and excellent and the pH range between 4.02 -4.30; indicative of good fermentation and absence of putrefaction, allowing the use of these species, without major alterations.